2022
DOI: 10.7759/cureus.22718
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Chronic Suppurative Otitis Media: A Complication Brewing Unnoticed

Abstract: Introduction: Chronic suppurative otitis media (CSOM) is a chronic infection of the middle ear cleft with a permanent perforation resulting in mucopurulent discharge and may include otalgia or fever, vertigo, hearing loss, and tinnitus. These compromise the quality of life of CSOM patients and affect their social communication and professional life also, which may induce social withdrawal and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…In a study conducted by Bakir et al in patients with CSOM and hearing loss, it was observed that CSOM patients with mild or moderate hearing loss have a poorer life quality and higher psychological problems [8]. Another cross-sectional study by Kumar et al analyzing depression in CSOM revealed a 30% prevalence of depression, with females being more commonly affected than males [9]. The majority of the patients in their study had mild depression.…”
Section: Discussionmentioning
confidence: 89%
“…In a study conducted by Bakir et al in patients with CSOM and hearing loss, it was observed that CSOM patients with mild or moderate hearing loss have a poorer life quality and higher psychological problems [8]. Another cross-sectional study by Kumar et al analyzing depression in CSOM revealed a 30% prevalence of depression, with females being more commonly affected than males [9]. The majority of the patients in their study had mild depression.…”
Section: Discussionmentioning
confidence: 89%